Development and Validation of a Novel Prognostic Score Based on Thrombotic and Inflammatory Biomarkers for Predicting 28-Day Adverse Outcomes in Patients with Acute Pancreatitis - Han T; Cheng T; Liao Y; He Y; Liu B; Lai Q; Pan P; Liu J; Lei C; Cao Y (Dove Medical Press, 2022)
Tianyong Han,1,* Tao Cheng,1,* Ye Liao,2 Yarong He,1 Bofu Liu,1 Qiang Lai,1 Pan Pan,1 Junzhao Liu,1 Chenxi Lei,1 Yu Cao1 1Emergency Department, West China Hospital of Sichuan University, Chengdu, Sichuan, People's Republic of China; 2Medical Intensive Care Unit, West China Hospital of Sichuan University, Chengdu, Sichuan, People's Republic of China*These authors contributed equally to this workCorrespondence: Yu CaoEmergency Department, West China Hospital of Sichuan University, 37 Guoxue Lane, Wuhou District, Chengdu, 610041, Sichuan, People's Republic of China, Tel +86 28-85422288, Email caoyu@wchscu.cnBackground: Acute pancreatitis (AP) is a multifactorial disease that is associated with substantial morbidity and mortality. Thrombosis and inflammation are involved in the development and progression of AP.Aim: To develop and validate a novel and simple scoring system for predicting 28-day adverse outcomes in AP patients based on a thrombotic and an inflammatory biomarker.Methods: A single-center, retrospective cohort study was used to establish the new scoring system (thrombo-inflammatory prognostic score; TIPS), and another study was used to verify it. The study end points were 28-day mortality, requirement for mechanical ventilation (MV), persistent organ failure (POF), and admission to the intensive care unit (AICU). Receiver operating characteristic (ROC) curves was drawn to validate the predictive value of the TIPS. The performance of the TIPS was compared with that of conventional predictive scoring systems. Logistic regression models were used to investigate the relationship between the TIPS and the different end points.Results: Among 440 patients with AP in the derivation group, 27 patients died within the 28-day follow-up period. Prothrombin time (PT) and interleukin-6 (IL-6) were used to calculate the TIPS. The TIPS (AUC=0.843) showed a performance comparable to that of the more established APACHE II (AUC=0.841), SOFA (AUC=0.797), BISAP (AUC=0.762), and Balthazar CT (AUC=0.655) in predicting 28-day mortality in AP. The 28-day mortality and the incidence of MV, POF, and AICU were significantly higher among patients with a higher TIPS (P< 0.001). The results of logistic regression analyses indicated that the TIPS was independently associated with the risks of 28-day mortality, AICU, MV and POF.Conclusion: The TIPS can enable prediction of 28-day adverse clinical outcomes with AP patients in the ED.Keywords: acute pancreatitis, prognosis, clinical outcomes, thrombosis, inflammation